Simplifying the nomenclature of Sorbus sensu lato: new nomenclatural solutions in Aria and Hedlundia (Rosaceae) - Mosyakin S.L.; Fedoronchuk M.M.; McNeill J. (Ukrainian Botanical Journal, 2025)
Various options for generic delimitation in Maleae (Rosaceae), specifically the taxa earlier included in Sorbus L. s. l., are discussed. Following the positive decision of the General Committee regarding our recent proposal to conserve the name Aria (Pers.) Host against the earlier names Chamaemespilus Medik. and Torminalis Medik., we conclude that for simplification of the taxonomic schemes and nomenclature in the group of Sorbus and its relatives, an expanded circumscription of Aria (including Chamaemespilus and Torminalis) is desirable; in particular, for preserving numerous names already available in Aria, especially those used for better known species. The European taxa of Sorbus s. l. accepted by Sennikov and Kurtto (2017) and in Atlas Florae Europaeae mostly in hybridogenous genera Karpatiosorbus Sennikov & Kurtto (combining in their genomes the subgenomes of the segregate genera Aria and Torminalis) and Majovskya Sennikov & Kurtto (with subgenomes of Aria and Chamaemespilus) are here transferred to Aria s. l. The names applied to hybridogenous genera Normeyera Sennikov & Kurtto and Scandosorbus Sennikov (≡ Borkhausenia Sennikov & Kurtto, nom. illeg.) that supposedly emerged from hybridization events combining Aria × Chamaemespilus × Sorbus and Aria × Sorbus × Torminalis, respectively, are here treated as synonyms of the hybridogenous generic name Hedlundia Sennikov & Kurtto (Aria s. l. × Sorbus), and the taxa earlier treated in Normeyera and Scandosorbus are here transferred to Hedlundia. In total, 104 new species-rank combinations are validated: 91 in Aria and 13 in Hedlundia. Comments are provided on hybrids (but not for hybridogenous species) between Aria and Sorbus, for which the nothogeneric name ×Arsorbus Su Liu & Z.H. Feng was recently proposed.